The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ijcs.12841
|View full text |Cite
|
Sign up to set email alerts
|

When transparency pays off: Enticing sceptical consumers with two‐sided advertising

Abstract: It has been generally assumed that higher levels of scepticism towards advertising invariably lead to higher resistance to advertising appeals. The main purpose of the present research was to examine whether highly sceptical consumers' resistance can be overcome by appeals associated with higher credibility. We tested our hypotheses using message sidedness as an advertising variable that has been associated with higher (two-sided) versus lower (one-sided) credibility. In three experimental studies, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…27,28 This finding may indicate that using transparent messaging and acknowledging uncertainty may be even more effective than other messages tested among those who are skeptical or lean against vaccination. 26,[29][30][31] Limitations Our study had several potential limitations. First, the sample represents a convenience sample of adults across the United States who agreed to be included in the online panel recruitment approach and participate in this particular study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…27,28 This finding may indicate that using transparent messaging and acknowledging uncertainty may be even more effective than other messages tested among those who are skeptical or lean against vaccination. 26,[29][30][31] Limitations Our study had several potential limitations. First, the sample represents a convenience sample of adults across the United States who agreed to be included in the online panel recruitment approach and participate in this particular study.…”
Section: Discussionmentioning
confidence: 94%
“…27,28 This finding may indicate that using transparent messaging and acknowledging uncertainty may be even more effective than other messages tested among those who are skeptical or lean against vaccination. 26,29 -31…”
Section: Discussionmentioning
confidence: 99%
“…For example, an influencer who is well-known Third, while our study does not examine individual characteristics, future studies may investigate moderators for the effects of message source and product benefit appeals. For instance, the level of persuasion knowledge, involvement, and skepticism (Hernandez et al, 2023) may affect consumers' attitude, intention, and behavior toward the donation campaign. For example, prior research has found that awareness of persuasive intention (i.e., disclosure) leads to a lower attitude and intention to share the post (Evans et al, 2017).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…As a result, there is a growing literature examining the conditions under which two-sided messages can be more persuasive and positively influence consumer evaluations. Prior research suggests that two-sided messages are perceived more favorably among consumers with high levels of skepticism (Hernandez et al ., 2023), self-confidence (Huertas and Hanna, 2020), involvement (Eisend, 2022; Pham et al ., 2016), and need for cognition (Florack et al ., 2009; Kao, 2011). However, these studies tend to focus on consumer-level differences that are relatively stable, and which marketers cannot fully control to develop effective communication strategies.…”
Section: Introductionmentioning
confidence: 99%